Anti-site disorder and physical properties in microwave synthesized RE2Ti2O7 (RE = Gd, Ho) pyrochlores. Issue 104 (11th November 2015) - Gómez-Pérez, Alejandro; Prado-Gonjal, Jesús; Muñoz-Gil, Daniel; Andrada-Chacón, Adrián; Sánchez-Benítez, Javier; Morán, Emilio; Azcondo, María Teresa; Amador, Ulises; Schmidt, Rainer
<x xml:space="preserve">Abstract</x> In this work we report on the microwave assisted synthesis of nano-sized Gd2Ti2O7 (GTO) and Ho2Ti2O7 (HTO) powders from the RE2Ti2O7 pyrochlore family (RE = rare earth) and their physical properties.